ANALISIS PENGARUH FAKTOR SOSIAL DAN EKONOMI TERHADAP RUMAH TANGGA MISKIN DI KABUPATEN GIANYAR TAHUN 2017-2021 - Saraswati, Ni Made Desya; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 4 (2023): Vol.12.4.APRIL.2023[231-310]DO - 10.24843/EEP.2023.v12.i04.p03, 2023)
Gianyar Regency is one of Indonesia areas that is concern by the government. The research motivated by the increased of poor households population in several years. The purposes are to obtain empirical evidence regarding the relationship of education level, income and unemployment rate simultaneously and partially in poor households, also variables that has a dominant effect with Gianyar Regency as the research location. The study used purposive sampling that the 100 sampled households must included in 2021’s poor households category. This research used Multiple Linear Analysis as data analysis technique. Based on the research results, the relation of education level, income and unemployment rate simultaneously has a significant effect on poor households, the relation of education level and income has a positive effect, and the relation of the unemployment rate has a negative effect on poor households. The research implications are this research is in line with the Culture of Poverty Theory, this research providing policy implications for the government to organize programs to encourage changes in people mindset in the aim of driving economic activity, paying attention on employment, education and income sector which has potential to reduce the existence of poor households in Gianyar Regency, Bali. keyword : Poor Households, Education, Income, Unemployment Klasifikasi JEL: G51, I25, D31, E24